Reflections on peacebuilding interventionism: State- and nationbuilding dilemmas in Southern Sudan (2005 to the present) - Ylönen, A. (Global Change, Peace and Security, 2016)
In 2005 Southern Sudan emerged from a long period of protracted civil war. The Comprehensive Peace Agreement marked the beginning of a period of post-war peacebuilding concentrating on statebuilding. However, since 2005, the much-needed gradual process of building a unified nation and inclusive national identity has been largely neglected. Instead, there has been emphasis on achieving ‘peace-through-statebuilding’ that has contributed to a highly exclusive social, economic, and political order dictated by the leadership of the dominant rebel movement turned government, the Sudan People's Liberation Movement/Army (SPLM/A). This essay reflects on peacebuilding interventionism, and state- and nationbuilding in Southern Sudan since 2005. It argues that this overall process dictated by the SPLM/A leadership, focusing on security and state, excluded the majority of Southern Sudanese from the peace dividend and economic and political opportunities. Further, the exclusive top-down SPLM/A-centric view of the nation marginalized part of the population and contributed to the continuing political instability and armed violence orchestrated by the leading individuals and other military men.